Pengaruh Pemberian Dzikir Tahlil terhadap Penurunan Kecemasan pada Pasien Pra Operasi di Rumah Sakit Umum Daerah Meuraxa Kota Banda Aceh - Miftah Khoirah; Urip Pratama; Nurul Amna (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Preoperative anxiety can lead to increased blood pressure, accelerated heart rate, and bleeding. One of the non-pharmacological interventions that can be provided is dhikr therapy, particularly tahlil dhikr (repeated recitation of La ilaha illallah). This study aims to determine the effect of tahlil dhikr on reducing anxiety in preoperative patients. This research is a quantitative study with a quasi-experimental design, using a one-group pretest-posttest approach. Data collection was conducted from May 22 to May 27, 2025, at Meuraxa Hospital. The population in this study consisted of 270 patients scheduled for surgery at Meuraxa Hospital, Banda Aceh, with a sample of 73 respondents selected through random sampling. The research instruments used were the Standard Operating Procedure (SOP) for Tahlil Dhikr Therapy and the Depression Anxiety Stress Scale 21 (DASS-21) questionnaire, which had a Cronbach’s Alpha score between 0.6 – 0.7 and was considered reliable with a result > 0.6. The results showed a decrease in the intensity of anxiety after the administration of tahlil dhikr. Data analysis using the Wilcoxon Signed-Rank Test showed a p-value = 0.000 (≤ 0.05), indicating a significant effect of tahlil dhikr on reducing preoperative anxiety among patients at Meuraxa Hospital, Banda Aceh. The study recommends the integration of tahlil dhikr as an alternative method for reducing anxiety in preoperative patients.